The Role of Zakat and Success Factor for Muallaf Conditions: An Analysis in Selangor, Malaysia - Fuadah Johari; Muhammad Ridhwan Ab. Aziz; Ahmad Fahme Mohd Ali (Universiti Sains Islam Malaysia, 2024)
In Selangor, zakat assistance to the new converts begins from the first day they become Muslims. The new Muslim would be immediately helped with MYR 500.00 monthly allowance for five years until they manage to act in accordance with Allah's orders and to perform worshipping (Mukallaf). The main problem statement is, how the effectiveness of zakat distribution among muallaf was?. Thus, this article presents structural equation models for effectiveness of zakat distribution among muallaf in Selangor. The formation of the models consists of the condition of the muallaf and success factors as well as the income before and after zakat distribution towards the muallaf, which are the observed variable. This specification will able to examine the predictors of differences between income without zakat and income with zakat. The Muallaf really need and seek for help from the Muslim especially in Muslim country in terms of economic strength and support. Thus, developmental programs are crucial in order to support them physically and mentally. An effective program can be an instrument to equip them with negative perception that they received after becoming a Muslim. The main objective of this article is to explore the effectiveness of muallaf development programs organized in Selangor, this article uses the crosstabs methods based on several critical success factors. The method been use in this research is mix method by conducted through in-depth interviews with selected Muallaf from a variety of cultural backgrounds, living in the area of Selangor, Malaysia. Then the next phase, this article conducted set of survey questionnaires among 80 respondents to confirm the findings. The respondents were randomly selected from Selangor Zakat Centre (SZC) zakat recipient's list from the New Converts category for nine districts of Selangor in 2013. The main finding of this article indicates that Muallaf who are receiving zakat assistant are able to manage successfully in their economics life and manage to assist their non-Muslims family for solving family problem as a result of conversion to Islam as well as helping them out from poverty.